(untitled) (Journal of the College of Basic Education, 2023)
The aim of the research is introducing the construction values of Baghdad University students i.e (Arts College- Fine Arts CollegePharmaceutics College – Medicine College – Administration and Economy College), and its relation of ambitions of the students according the variables of sexes and specialists of the college i.e(scientifichumanity).The sample of the research has included 120 students (60 males and 60 female) . it has been applied the Arabic Rokbish scale and Ambitions Rasoul scale. Also ,it has been adopted the suitable statistical methods for reaching the results’ research.The following results are:1-There are no significance statistical differences of construction values of the sample according to the sexes and specialists college variables.2- There are no scientific statistical differences of ambitions level of the sample according to sexes and specialists college variables.3-There is significance relation between the construction values and ambitions level of the sample.Thus, the recommendations of the research are:1- Supporting the values which the Baghdad University students have preferred.2-Reinforment the Original values which are affecting the ambition level of the students through the curriculums.